Energy storage system (ESS) design for a building microgrid - Hu, Xingyu (2018)
Over the last decade, generation of electricity has grown rapidly all over the world. Due to the limitation of fossil fuels and other non-renewable energy, the need to adopt other alternative energy sources is imminent. A number of researches have been conducted to find an economical and practical energy source in last several decades. The system of Microgrid by using some renewable resources to generate power draws specialists concern. Moreover, comparing with centralized national grid, Microgrid will not cause large area power failure and it is more reliable. Energy storage system plays an important role in Microgrid. It`s supporting remote sites by using the energy generated from renewable sources. This project will design an Energy Storage System (ESS) with renewable energy generation (PV system) for a selected building Microgrid. By adding this ESS system into Microgrid, the surplus energy generated by PV panel can be stored in off-peak hours, and discharge the electricity and reuse them in peak hours. It`s not only reduced the wastage of electricity but also reduce the loss during the transmission and increase the service life of power generation equipment. Total loads and the maximum demands for a selected residential building will be calculated. Where the renewable energy will be produced from solar irradiation on the roof top and calculated based on the area and weather condition. The size of energy storage will be selected based on total energy consumed by load, energy produced from PV and energy supplied from power grid. The operation of ESS will be determined based on the time varying price of Singapore power market. At last, Software HOMER will display simulation results in various tables and charts, to configurations and evaluate the economic and technical advantages.